PEMANFAATAN KULIT JENGKOL SEBAGAI ADSORBEN DALAM PENYERAPAN LOGAM Cd (II) PADA LIMBAH CAIR INDUSTRI PELAPISAN LOGAM - Setiaty Pandia, Budi Warman (Universitas Sumatera Utara, 2016)
The aim of this research is to study the effect of activation processes to iodine number of ngapi nut peel adsorbent and to study the optimum adsorbent mass to reduce metallic Cadmium (Cd) concentration in electroplating wastewater. Ngapi nut peel was cleaned and mashed to a size of 100 mesh of sieve tray and then activated using nitric acid (HNO3) 4 N with specific ratio ngapi nut peel : nitric acid while heated at specific activation temperature and duration. Adsorbent dried in oven at specific temperature and duration of drying. Adsorbent with optimum iodine number then used in batch adsorption that carried out by using variations of mass in 50 mL of wastewater. The results showed that the optimum ratio of ngapi nut peel : nitric acid is 20:1 mg/mL at activation temperature 90°C, duration of activation 120 minutes, drying temperature 110 °C and duration of drying 120 minutes with iodine number 634.50 mg/g. The optimum mass of adsorbent is 1 g with capacity of adsorbent 1,326 mg/g.